PENINGKATAN PENGAJARAN PEMBELAJARAN TAFSIR ALQUR’AN SURAT AL- BAQOROH MELALUI LAGU QUR’ANY DI MTs. FIRDAUS PANGALENGAN KABUPATEN BANDUNG - Uus Rustiman (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
This service activity aims to implement the teaching of Al-Qur’an Interpretation of Surah Al-Baqarah through the Qur’ani song approach at MTs. Firdaus Pangalengan, Bandung Regency. This activity is focused on the planning, implementation, and evaluation stages of the teaching method. The Al-Qur’an Interpretation method which was previously more commonly used by adults such as students, university students, lecturers, and scholars, is now being applied to children. Evaluation is done by asking students to memorize and then write down their understanding of the Al-Qur’an Interpretation material being taught. This approach shows positive results in increasing students’ interest in learning and understanding of Tafsir Al-Qur’an. By utilizing Al-Qur’an songs, this teaching method is able to present an interesting and interactive learning experience for children. This activity provides a new alternative in the approach to teaching religion, so that it is relevant to the characteristics and development of children. The results of this dedication show that the learning plan for Tafsir Al-Qur’an Surah Al-Baqarah through the Qur’anic song approach involves formulating learning objectives, selecting appropriate teaching materials, methods and media to support the teaching and learning process. In practice, the teachers invite students to read Surah Al-Baqarah, starting with reading a short prayer and sholawat as an opening. The teaching approach through Al-Qur’an songs gives students the opportunity to actively participate, sing along to the songs, and practice together